'Youngsplaining' and moralistic judgements: exploring ageism through the lens of digital 'media ideologies'. Issue 4 (29th April 2022) - Comunello, Francesca; Rosales, Andrea; Mulargia, Simone; Ieracitano, Francesca; Belotti, Francesca; Fernández-Ardèvol, Mireia
Abstract: In this paper, we explore ageist depictions of both young and older people as they emerge from discourses addressing 'other people's' digital media usage practices. We carried out eight focus groups (four with teenagers, four with people aged 65 or older) in two southern European cities (Rome and Barcelona). By negotiating the affordances and constraints of (digital) tools and platforms, people develop their own usage norms and strategies, which might – or might not – be intersubjectively shared. Discourses surrounding usage practices and norms tend to refer to what people understand as an appropriate way of using digital platforms: these discourses proved to be powerful triggers for expressing ageist stereotypes; 'the others' were depicted, by both teenage and older participants, as adopting inappropriate usage practices (with regard to content, form, skills and adherence to social norms). These reflections proved to have broader implications on how other age cohorts are perceived: participants tended to take discourses on digital media usage as an opportunity for making generalised judgements about 'the others', which address their manners, as well as their attitude towards communication and social life. Inter-group discrimination processes and ageist stereotypes play a major role in shaping the strong moralistic and patronising judgements expressed by older and younger participants towards 'the other' age cohort.